Penerapan Activity-Based Costing Pada Bengkel Las dan Konstruksi “ Artomoro ” Pekalongan - Akhmad Pujiono; Djauhar Edi P (Neraca, 2022)
Activity-Based Costing (ABC) is an accounting method that can be used to find the total cost of activities required to make a product. This study uses a descriptive qualitative method and aims to help SMEs welding and construction workshops "Artomoro" in applying the activity-based costing method as a tool for accounting calculations in reducing the cost of producing a product, and comparing it with manual calculations (Traditional-Based Costing). Activity-based costing methods provide more accurate and informative product costs, leading to more accurate measurement of product profitability and better informed strategic decisions about pricing, product lines, and market segments. Furthermore, ABC can help workshop owners identify and control the cost of unused capacity. From the results of the study, it can be seen that by using the activity-based costing method, the SMEs welding and construction workshop "Artomoro" will have a positive impact in the preparation of the cost of production, namely in the imposition of factory overhead costs on each product. From the calculations that have been made, it can also be seen that activity-based costing is a good alternative for the “Artomoro” welding and construction workshop SMEs in order to maximize their profits by using the right cost of production system in charging factory overhead costs.Keywords: Activity based costing, Traditional-Based Costing, MSME